Recency Matematis Mahasiswa Calon Guru Matematika dalam Menyelesaikan Masalah Bergambar - Darmawan, Puguh; Yohanes, Barep (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2022)
Recency is a conclusion that is preceded by similar events. Recency is very important for prospective mathematics teacher students because it avoids thinking errors/cognitive biases. This research is a qualitative research that aims to determine the emergence of positive and negative recency in prospective students of mathematics teachers. The research was conducted by providing pictorial problems for prospective mathematics teacher students and based on indicators grouped into positive recency and negative recency. The results of the study indicate that students who experience positive recency occur because of learning experiences and similar events that are believed to be. Negative recency occurs because of doubtful learning experiences and similar events. Keywords: mathematical recency, teacher candidate, pictorial problem, probability